Review of Cordylocras Kozlov (Hymenoptera, Diapriidae): with a new species and redescription of C. mirabilis Kozlov - Paz, Víctor De; Chemyreva, Vasilisa; Kolyada, Victor; Baños-Picón, Laura; Asís, Josep D.; Popovici, Ovidiu Alin (Zootaxa, 2024)
The female of Cordylocras abscondita de Paz & Popovici sp. nov., is described and illustrated from the province of Salamanca (Western Spain). The female and male of C. mirabilis Kozlov, 1966 are redescribed and illustrated and new data on the distribution, and photographs of the holotype are provided. The possible biology of Cordylocras species is discussed.